1986
DOI: 10.2466/pr0.1986.59.2.899
|View full text |Cite
|
Sign up to set email alerts
|

Refutational Messages on Donor Cards: A Test of Boomerang Effects

Abstract: The use of refutational messages was suggested in a recent discussion about public communication campaigns as an instrument in recruiting donor-card holders. Characteristically such messages not only point out arguments in favour of filling in a donor card, but they also refute potential counterarguments. In the light of normative altruism models this particular sort of message runs a high risk of boomerang effects. In this experiment it was hypothesised that, specifically for subjects showing a strong tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Health care recipients do not always agree with clinician recommendations and this dynamic may reveal much about their shared interaction. Successful use of refutations can neutralize reservations or build resistance to recommendations (Boster, Levine, & Kazoleas, 1993; Kazoleas, 1993; Winkel & Huismans, 1986). SCCAP coding includes identification and description of persuasive arguments and any corresponding refutation from any speaker.…”
Section: Communication Theory Used To Construct the Sccapmentioning
confidence: 99%
“…Health care recipients do not always agree with clinician recommendations and this dynamic may reveal much about their shared interaction. Successful use of refutations can neutralize reservations or build resistance to recommendations (Boster, Levine, & Kazoleas, 1993; Kazoleas, 1993; Winkel & Huismans, 1986). SCCAP coding includes identification and description of persuasive arguments and any corresponding refutation from any speaker.…”
Section: Communication Theory Used To Construct the Sccapmentioning
confidence: 99%
“…This finding suggested that effective messages need to accompany requests for signing: messages which present both the beneficial aspects of organ donation and refutations of false beliefs about its perceived negative aspects. The superior effects of such messages on willingness were demonstrated by Winkel (1 984), Winkel and Huismans (1986), and Deuser (1989). For example, Deuser's study compared the effect of a true statement regarding the nutritional value of red meat to a foot-in-the-door procedure and to a two-sided message.…”
mentioning
confidence: 97%
“…1986), knowledge (e.g., Horton & Horton, 1990. and persuasive message styles (e.g., Winkel, 1984;Winkel & Huismans, 1986). Shortcomings o f these approaches include the failure to require that family serves as a witness, the fact that only a small percentage of those wishing to donate actually have donor cards (Overcast et al, 1984).…”
mentioning
confidence: 99%